Efforts To Improve Adolescent Reproductive Health Skills At Azzahra Islamic Smp It School Kutacane - Yusnika Damayanti; Yessy Syahradesi Br Tambunan (Jurnal EduHealth, 2023)
Skills regarding reproductive health in adolescents can measure the level of knowledge, attitudes and actions of adolescents regarding reproductive health issues. Adolescents need to understand their reproductive health, so that adolescents know their bodies and reproductive organs. Good knowledge and attitudes about adolescent reproductive health are the basis for adolescents to be able to avoid negative risks such as unhealthy sexual behavior and sexually transmitted diseases. This research aims to identify reproductive health skills in adolescents at SMP IT Azzahra Islamic School Kutacane. The sample studied was 46 people. This research was conducted at SMP IT Azzahra Islamic School Kutacane in September 2023. Data collection was carried out using a questionnaire compiled by the researcher himself based on literature review, observations and interviews with students consisting of demographic data, a questionnaire to measure teenagers' skills regarding reproductive health , and a questionnaire to measure teenagers' knowledge and attitudes about reproductive health using a Likert scale. The results showed that 16 respondents (34.79%) had good skills about adolescent reproductive health, while 29 respondents (63.04%) had sufficient skills about adolescent reproductive health, and 1 respondent (2.17%) had knowledge not enough. The research results showed that 1 respondent (2.17%) had a good attitude about adolescent reproductive health, while 45 respondents (97.83%) had a fair attitude about adolescent reproductive health. The conclusion obtained from this research is that efforts to improve adolescent reproductive health are quite good.